Social capital and human development: a meta analysis in Iran - Babaei, Hamidreza; Zomorrodian, Amir Hossein; Gill, Sarjit S.; Ahmad, Nobaya; Falahati, Leila (Marsland Press, 2011)
This meta-analysis aims to assess the influence of social capital on the Human Development Index, Human Poverty Index, and Gender-related Development Index in Iran. The results reveal a positive and significant relationship between social capital and the human development index (HDI). The effect of social capital on the Human Poverty Index (HPI) was negative and significant. However, no significant relationship was found between social capital and the Gender-related Development Index (GDI).